2014
DOI: 10.1186/1756-0500-7-181
|View full text |Cite
|
Sign up to set email alerts
|

Applying a correction procedure to the prevalence estimates of overweight and obesity in the German part of the HBSC study

Abstract: BackgroundPrevalence rates for overweight and obesity based on self-reported height and weight are underestimated, whereas the prevalence rate for underweight is slightly overestimated. Therefore a correction is needed. Aim of this study is to apply correction procedures to the prevalence rates developed on basis of (self-reported and measured) data from the representative German National Health Interview and Examination Survey for Children and Adolescents (KiGGS) to (self-reported) data from the German Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
9
0
3
Order By: Relevance
“…Therefore, this procedure [ 10 ] was replicated in the present paper in order to derive a new correction formula for KiGGS Wave 1, since the patterns of underreporting might vary over time. It has also been applied or replicated, respectively in other German studies in order to get improved prevalence estimates [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this procedure [ 10 ] was replicated in the present paper in order to derive a new correction formula for KiGGS Wave 1, since the patterns of underreporting might vary over time. It has also been applied or replicated, respectively in other German studies in order to get improved prevalence estimates [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that subjective reports tend to underestimate true BMI and that the prevalence of overweight/obesity eventually tends to be under-reported 37 . Therefore, a method suggested by a prior study was used to correct the self-reported BMI 38 . The corrected BMI was then used to determine overweight and obesity.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have shown that the validity of such transportability is increased when equations are derived from the same population and in a similar time period. [23][24][25] We used available parameters in the CHMS (e.g. age and history of a live birth) to obtain the most suitable comparison group.…”
Section: Strengths and Limitationsmentioning
confidence: 99%